Back to the Future - Part 1. The medico-legal autopsy from ancient civilization to the post-genomic era - Cecchetto, Giovanni; Bajanowski, Thomas; Cecchi, Rossana; Favretto, Donata; Grabherr, Silke; Ishikawa, Takaki; Kondo, Toshikazu; Montisci, Massimo; Pfeiffer, Heidi; Bonati, Maurizio Rippa; Shokry, Dina; Vennemann, Marielle; et al. (International journal of legal medicine, 2017)
Part 1 of the review “ Back to the Future ” examines the historical evolution of the medico-legal autopsy and microscopy techniques, from Ancient Civilization to the Post-Genomic Era. In the section focusing on “ The Past ”, the study of historical sources concerning the origins and development of the medico-legal autopsy, from the Bronze Age until the Middle Ages, shows how, as early as 2000 BC, the performance of autopsies for medico-legal purposes was a known and widespread practice in some ancient civilizations in Egypt, the Far East and later in Europe. In the section focusing on “ The Present ”, the improvement of autopsy techniques by Friedrich Albert Zenker and Rudolf Virchow and the contemporary development of optical microscopy techniques for forensic purposes during the 19th and 20th centuries are reported, emphasizing, the regulation of medico-legal autopsies in diverse nations around the world and the publication of international guidelines or best practices elaborated by International Scientific Societies. Finally, in “The Future” section, innovative robotized and advanced microscopy systems and techniques, including their possible use in the bio-medicolegal field, are reported, which should lead to the improvement and standardization of the autopsy methodology, thereby achieving a more precise identification of natural and traumatic pathologies.